Comparative Analysis of Abrasive Materials and Polishing System on the Surface Roughness of Heat-Polymerized Acrylic Resins - Onwubu, Stanley Chibuzor; Mdluli, Phumlane Selby (European Journal of Dentistry, 2021)
Objective The aim of this in vitro experiment was to see how the operator's manual skills, polishing equipment, and abrasive materials affected the surface roughness of denture base resins.Materials and Methods Forty polymethyl methacrylate (PMMA) specimens were created and polished by using two different polishing systems, namely hand and automatic polishing machines. Three operators hand-polished 30 of specimens with eggshell powder and pumice, while 10 were automatically polished (n = 5). A profilometer was used to determine the average surface roughness (Ra) after polishing. The Ra values for the specimens hand-polished were analyzed by using paired sample testing. The Ra values for all polished specimens were analyzed by using a one-way ANOVA. Differences between the two abrasive materials as well as the polishing system were determined by using the Bonferonni tests (p = 0.05).Results and Conclusion For the PMMA specimens hand-polished, there was a strong connection in the Ra values. There were also significant variations in the Ra values across the three operators (p < 0.001). The automated technique created a substantially smoother surface than the traditional technique (p = 0.001). The greatest Ra values (0.20 µm) were found in specimens polished traditionally by using pumice, whereas the lowest Ra values (0.04 µm) were found in specimens polished mechanically with eggshell powder. The automated polishing system was the most effective polishing method when the Ra values were connected to the level of smoothness.
Keywords: abrasive materials; eggshell powder; polishing system; pumice; surface roughness